Pelatihan Peningkatan Kompetensi Bidang Sistem Kendali Menggunakan Modul Arduino Di SMK Pangeran Antasari Balikpapan - Fathur Zaini Rachman; Suhaedi Suhaedi; Hadiyanto Hadiyanto; Ihsan Ihsan (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The activity at the "Pangeran Antasari Balikpapan" Vocational School has several objectives: improving teacher competency by training and testing directly on Arduino-based practice modules that have multi-input and multi-output peripherals that have extensive functions for applications in automatic control systems. Analysis and discussion to partners there are 2 main problems, the problem of automation technology and teacher competence. The problem of automation technology is solved by training practice modules that are useful as learning media in the field of automatic control systems and can be implemented for various applications. The problem of teacher competence with technology updates is solved by the development of learning media so that the teacher is able to create and innovate in the control system. The method used in this activity is discussion, explanation, demonstration, practice, and observation.